Epidemiological, Clinical and Therapeutic Characteristics of Patients undergoing Goiter Surgery in Beni, Democratic Republic of the Congo - Michel Kalongo Ilumbulumbu; Reginald Moreels; Piet Bekaert; Moise Muhindo Valimungighe; Joël Kambale Ketha; Franck Katembo Sikakulya; Alexandre Amini Mitamo (Archives of Current Research International, 2018)
Background: Iodine deficiency disorder is one of the world’s public health problems and affects millions of people in developing countries. Its diagnosis is often easy, while its management is still difficult in our countries. This work aims to determine the epidemiological, clinical and therapeutic characteristics of patients undergoing goiter surgery at Beni General Referral Hospital, DRC. Methods: It was a prospective descriptive cross-sectional study that was carried out from November 2016 to November 2017 at Beni referral Hospital, in Democratic Republic of the Congo. Results: Overall, 23 patients underwent goiter surgery. The predominance of women demonstrated in 95.7% and the most affected age group was 40 years and above. The majority of patients came from rural areas and was farmers. Physical asthenia and palpitation were the most important chief complaints in 39.2% and 30.4% respectively. The diving, multinodular and toxic goiters were more founded at stage IV or no defined in most of the cases. General anesthesia combined with oro-tracheal intubation was the type of anaesthesia used in all cases. Subtotal lobectomy and subtotal thyroidectomy were the surgical techniques used. All postoperative suites were favourable, with only one case of tracheomalacia as a complication. Conclusion: Iodine deficiency disorder remains a public health problem in our environment. The sensitization of the population who is vulnerable and the thorough knowledge of its management by caregivers are of paramount importance in our country.